2022
DOI: 10.1186/s12902-022-00955-2
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of the RAAS affect bone metabolism in patients with primary aldosteronism, Gitelman syndrome and Bartter syndrome

Abstract: Background Components of the RAAS may influence bone metabolism. Different roles of the RAAS are found in patients with primary aldosteronism (PA), Gitelman syndrome (GS) and Bartter syndrome (BS). We collected inpatient medical records including 20 patients with Gitelman syndrome (GS group), 17 patients with Bartter syndrome (BS group) and 20 age-matched patients with primary aldosteronism (PA group). We found the following results. (1) PA patients had significantly higher serum magnesium, pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…However, Petramala et al (26) and Salcuni et al (28) found that the osteopenia and OP rates in PA patients were significantly higher than in EH patients, healthy subjects, and those with adrenal nonfunctioning tumors (NFAs). This was confirmed by another study comparing patients with PA and secondary aldosteronism (9).…”
Section: Risk Of Op In Pa Patientssupporting
confidence: 57%
“…However, Petramala et al (26) and Salcuni et al (28) found that the osteopenia and OP rates in PA patients were significantly higher than in EH patients, healthy subjects, and those with adrenal nonfunctioning tumors (NFAs). This was confirmed by another study comparing patients with PA and secondary aldosteronism (9).…”
Section: Risk Of Op In Pa Patientssupporting
confidence: 57%
“…Hyperreninemic hyperaldosteronism occurring in BS patients can also play a role, as both angiotensin II and aldosterone increase PTH secretion [ 20 ]. Along with chronic high PTH, excess aldosterone, as seen in primary hyperaldosteronism, can also have direct and detrimental effects in bone of BS patients, as osteoclasts, osteoblasts, and osteocytes express mineralocorticoid receptors [ 21 23 ]. Indeed, low bone mineral density has been described in patients with BS types 1 and 2, and life-long bone mineral density monitoring is being recommended [ 18 ].…”
Section: Discussionmentioning
confidence: 99%